MicroRNA-1269a Promotes Proliferation and Arrest of Apoptosis of Glioma Cells by Directly Targeting ATRX - Zhang, Yulian; Wang, Qi; Luo, Na; Liu, Jiang; Ren, Hongxiang; Shao, Xu; Zhang, Li; Yu, Yanbing (Frontiers in Oncology, 2020)
Glioma is one of the deadliest malignant brain tumors in adults worldwide. MicroRNA (miR) has been reported to be a pivotal regulator in human tumors. The aim of this study was to determine the expression, function, and mechanism of action of miR-1269a in glioma progression. The expression of miR-1269a was higher in both glioma cases reported in databases and glioma cell lines, and it was highly associated with poorer prognosis. Next, it was shown in vitro that mimic of miR-1269a could promote glioma progression and arrest apoptosis, whereas the inhibition of miR-1269a exhibited the opposite effects. In addition, miR-1269a was found to directly target ATRX chromatin remodeler by a dual-luciferase reporter assay. Moreover, ATRX overexpression could reverse the suppressive effects of miR-1269a on proliferation and apoptosis in vitro. In vivo subcutaneous xenograft tumor assay was also performed to confirm the phenotypes and molecular mechanism involved. Taking the findings together, our study implies that the miR-1269a/ATRX axis is a novel therapeutic target of glioma.